2008
DOI: 10.1080/17435390802296347
|View full text |Cite
|
Sign up to set email alerts
|

Functionally charged polystyrene particles activate immortalized mouse microglia (BV2): cellular and genomic response

Abstract: The effect of particle surface charge on the biological activation of immortalized mouse microglia (BV2) was examined. Same size ( Â850Á950 nm) spherical polystyrene microparticles (SPM) with net negative (carboxyl, COOH-) or positive (dimethyl amino, CH 3 ) 2 -N-zeta potentials were exposed to BV2 microglia (5Á20 ml/ml). Both stimulated an oxidative burst, increased Caspase 3/7 activity and caused inflammatory cytokine release. Ultrastructure indicated that SPM particles were phagocytosed as single particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…However, a considerable amount of agglomeration was observed in media as the particle size increased steadily to 514 nm for AuNS–MPS and 480 nm for AuNR–PEG. This agglomeration was caused by the high concentration of electrolytes in the media that effectively screened the electrostatic interaction between the gold nanomaterials and resulted in decreased colloidal stability. , The agglomerate structure of the spheres and rods as determined by static light scattering (SLS) showed fractal dimension D f of 2.57 ± 0.4 for the AuNS–MPS and 1.28 ± 0.08 for the AuNR–PEG (Table ), the mean and one standard deviation about the mean of three replicate measurements. The lower fractal dimension for the AuNR–PEG indicates that the agglomerates formed in media are loosely bound compared to more densely formed agglomerates in the case of AuNS–MPS, and the D f of 2.57 suggests diffusion-limited colloidal agglomeration was driving the formation of the AuNS–MPS agglomerates .…”
Section: Resultsmentioning
confidence: 99%
“…However, a considerable amount of agglomeration was observed in media as the particle size increased steadily to 514 nm for AuNS–MPS and 480 nm for AuNR–PEG. This agglomeration was caused by the high concentration of electrolytes in the media that effectively screened the electrostatic interaction between the gold nanomaterials and resulted in decreased colloidal stability. , The agglomerate structure of the spheres and rods as determined by static light scattering (SLS) showed fractal dimension D f of 2.57 ± 0.4 for the AuNS–MPS and 1.28 ± 0.08 for the AuNR–PEG (Table ), the mean and one standard deviation about the mean of three replicate measurements. The lower fractal dimension for the AuNR–PEG indicates that the agglomerates formed in media are loosely bound compared to more densely formed agglomerates in the case of AuNS–MPS, and the D f of 2.57 suggests diffusion-limited colloidal agglomeration was driving the formation of the AuNS–MPS agglomerates .…”
Section: Resultsmentioning
confidence: 99%
“…Particle surface charge may also influence particle translocation and cellular responses. Exposure of immortalized BV2 brain microglia to inert spherical polystyrene microparticles (SPM) with carboxyl (COOH-; net negative) or dimethyl amino ([CH 3 ] 2 -N-; net positive) zeta potentials resulted in oxidative burst, increased caspase activity, and release of inflammatory cytokines (Veronesi et al 2008). Gene expression analysis of these exposures revealed that a large number of genes altered were distinct to a specific functionalization (Veronesi et al 2008), suggesting that functionally charged particles can differentially activate cellular mechanisms in the CNS.…”
Section: Systemic Effectsmentioning
confidence: 99%